Contextual issues for vocational placement coordinators : some preliminary findings - Flett, Ross [Verfasser]; Biggs, Herbert [Verfasser] (My University, 1992)
"While vocational placement it seen as an important component of the rehabilitation process, the experience of being a vocational placement officer has not been well documented in New Zealand. In the present study, previously developed and validated measures of occupational stress (defined as responsibility pressure, quality concern, role conflict, and job vs non-job-conflict) and general life satisfaction were completed by 16 vocational placement officers employed by the Accident Compensation Corporation. Subjects also completed two open-ended questions assessing significant stresses in their work and strategies whereby stress could be reduced. There were high negative correlation between job stress and life satisfaction, and subjekts reported particularly high levels of role conflict in their work. Open-ended stresses identified by subjects included: time pressure/workload problems; difficulties with negative societal and employer attitudes to disability; problems with clients, and; personal motivation problems. Most strategies for stress reduction that were identified were concerned with creating more effective communication and decision making processes in the organizational environment. Problems and limitations of the present study are addressed and future research directions are identified." (author's abstract) ((en)) Bei 16 Arbeitsvermittlern der Accident Compensation Corporation Neuseelands wurden der berufliche Stress und die allgemeine Lebenszufriedenheit mit Hilfe zuvor entwickelter und validierter Messinstrumente erhoben. Die Versuchspersonen nahmen auch Stellung zu zwei offenen Fragestellungen, durch welche wesentliche Stressfaktoren in ihrer Arbeit und Strategien zur Reduzierung von Stress erfasst werden sollten. Es ergaben sich hohe negative Korrelationen zwischen beruflichem Stress und Lebenszufriedenheit; auf ein besonders hohes Ausmass von Rollenkonflikten bei der Arbeit wurde hingewiesen. Folgende Stressfaktoren wurden identifiziert: Probleme des Zeitdrucks/der Arbeitsbelastung, Schwierigkeiten mit negativen Einstellungen gegenüber Behinderung in der Gesellschaft und bei Arbeitgebern, Probleme mit Klienten und Probleme persönlicher Motivation. Die meisten Strategien, die zur Stressreduktion genannt wurden, bezogen sich auf die Herstellung effektiver Prozesse der Kommunikation und der Entscheidungsfindung in der organisatorischen Umgebung. Auf Probleme und Grenzen der Untersuchung wird hingewiesen. Hinweise für zukünftige Forschung werden gegeben. (IAB2)
Lebens- und Arbeitsumwelt von Arbeitsvermittlern für Behinderte - Erste Ergebnisse
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.1 Arbeitsteilung & -organisation; G 2.4 Sozialer Wandel; G 2.3 Wandel von Arbeit & Wirtschaft; Arbeitsvermittler; Arbeitszufriedenheit; Lebenssituation; Stress; Menschen mit Behinderung; Berufsproblem; Berufsrolle; Konflikt